NTRU Over Galois Rings - ÖZDEMİR, AHMET ŞÜKRÜ (WALTER DE GRUYTER GMBH, 2021)
As a cryptosystem, Nth Truncated Polynomial Ring (NTRU) is established on the fast and easy calculation. Improving the security is aimed by enlarging a ring where the processes execute and enhancing the nwnber of a private key and a public key. In this study, NTRU takes over the Galois rings and is analysed by adding a new private key.
Keywords: Vector field; complete lift; diagonal lift; pull-back bundle; cross-section; semi-cotangent bundle